CORELATION BETWEEN NEUROTICISM AND SUPERSTITIOUS BELIEF IN JAVANESE SOCIETY, INDONESIA: A CROSS-SECTIONAL STUDY - Saskia, Rara Asra Luthvi; Muhammad, Amri Hana (Journal of Community Mental Health and Public Policy, 2024)
Background: Superstitious beliefs which started from negative emotions appear to be related to the neuroticism personality in people who also have a tendency to negative emotions. Though both are not influenced by one another, they do share certain commonalities that are brought on by unfavourable feelings like worry, anxiety, and low self-esteem. Purpose: This study aims to reveal whether there is a relationship between the variable’s neuroticism and superstitious beliefs. Methods: This study used a neuroticism and superstitious belief scale which was created based on its aspects. This study used a cross-sectional quantitative research approach with a correlational design. It was conducted with a population of Javanese people who live in Javanese culture or claim to have Javanese culture. The studz used purposive sampling technique with a total of 219 samples. Result: The results of the hypothesis test for the variables neuroticism and superstitious belief showed that Pearson’s r value was 0.991. It means there was a positive relationship between the two variables in the perfect category. Conclusion: This study concludes that the results of neuroticism and superstitious beliefs in Javanese society were generally in the moderate category. Abstrak Latar Belakang: Superstitious belief yang berpangkal dari emosi negatif ini nampak memiliki keterkaitan dengan kepribadian neuroticism pada diri individu yang juga memiliki kecenderungan emosi negatif. Namun keduanya tidak mempengaruhi satu sama lain, melainkan memiliki kesamaan yang lahir melalui emosi negatif seperti kecemasan, ketakutan, kekhawatiran, serta ketidak percayaan diri. Tujuan: Bertujuan untuk melihat adakah hubungan antara variabel neuroticism dan superstitious belief. Metode: Menggunakan skala neuroticism dan superstitious belief yang dibuat berdasarkan aspek-aspeknya. Penelitian ini menggunakan pendekatan penelitian kuantitatif cross sectional dengan desain korelasional. Dilakukan dengan populasi masyarakat Jawa yang hidup dalam budaya atau mengakui berbudaya Jawa. Teknik pengambilan sampel menggunakan purposive sampling dengan jumlah 219 sampel. Hasil: Uji hipotesis variabel neuroticism dan superstitious belief menunjukan nilai Pearson’s r menunjukkan angka 0,991 yang artinya terdapat hubungan posittif antar dua variabel dalam kategori sempurna. Kesimpulan: Penelitian ini menunjukkan bahwa hasil neuroticism dan superstitious belief pada masyarakat Jawa secara umum berada dalam kategori sedang.